Organizational aspects of digitization projects in the Croatian public libraries - Vrana, Radovan (Array, 2011)
The article presents findings from the research in the Croatian public libraries on organizational aspects of digitization projects. Findings indicate that public libraries in Croatia are strongly dedicated to development of digital collections as soon as necessary conditions for launch of their digitization projects are met.